O Porto e os portuenses no final do séc. XX : ou as relações entre os homens e um ecossistema em entropia acelerada? - Monteiro, Ana (1990)
With this paper we don't pretend more than make an effort to come across and put in evidence some actual and perceptible manifestations of the Oporto’s ecossystem degradation. Looking to the triangle Climatic-Atmospheric Pollution-Health at Oporto from lst April 1987 till 31st March 1990 we want to show that human activities always lead to important environmental changes. Even if we adopt an optimistic point of vue about the existent risks for human survival in a near future, we can't avoid thinking about the unpleasant side effects of human activities at Oporto. Besides knowing the complexity inherent to each vertex of the triangle climatic-Atmospheric Pollution-Health, we tried to find, diagnosing and discussing, some hypothetic causal-effect relationships between some climatic variables, levels of SO2 and the manifestation of some pathologies.